Application of the differential Fabry–Perot interferometer in angle metrology. (20th January 2016) - Çelik, M; Şahin, E; Yandayan, T; Hamid, R; Akgöz, A; Özgür, B; Çetintaş, M; Demir, A
Abstract: A differential Fabry–Perot interferometer (DFPI) was applied for the detection of ultra-small angles in the level of nanoradian (nrad) precision. During application, down to 1 nrad angular steps were generated using the available high precision small angle generator (HPSAG) and these steps were detected using the frequency stabilised lasers as an alternative and outperforming method to conventional angle interferometers. The use of the DFPI provided the displacement measurements (further angular displacements through optical configuration) with picometre sensitivity free from linearity errors. A coefficient of 1.436 964  ×  10 −9 arcsec Hz −1 (about 7  ×  10 −6 nrad Hz −1 ) for the DFPI was calculated using the generated–measured traceable angular values of the HPSAG and various angular steps were measured by the DFPI using this coefficient. The tests were carried out up to the range of 0.5 arcsec (2500 nrad) in angular steps down to 1 nrad. The work is in progress under the SIB58 Angles project and aims to reduce the noise level of the HPSAG with further statistical process and later to extend the measurement range of the DFPI readings with the same optical configuration, rather than using different beam spacing configuration in the DFPI.